The relationship between customer satisfaction and loyalty in South African grocery stores - Simpson, Cade (My University, 2011)
The South African economy has, over the last 18 months, experienced severe change. The good times have been replaced with bad. The once buoyant consumer riding the crest of the wave and with an unquenchable appetite for debt, who revelled in the trappings of what money could buy, is long gone. In his or her place is a consumer riddled with debt, fighting for survival on the edge of the precipice, with only a teetering world economy for comfort. Liquidation auctions and notices of execution have become the weekly norm, with many people struggling to keep their ahead above water and living from one day to the next in hope. There can be no doubt that, in the current market conditions, for a retailer to develop customer satisfaction and/or loyalty is of paramount importance, given the proven repeat purchasing behaviour associated within these two constructs. With this in mind then, the research sets out to determine what the dimensions of customer satisfaction and customer loyalty are and, having identified these, whether there is a correlation which exists between these two constructs. The research was conducted by means of a survey, with 249 questionnaires being completed. The data was then analysed by way of exploratory Factor Analysis and Interdependence Factor Analysis. Two factors were found from the exploratory Factor Analysis on customer satisfaction. These were termed ―Value-Based Retailing” and “Service-Based Retailing”. A limited number of dimensions related to customer satisfaction either did not load or loaded partially on the final two factors, and as a result the research proposition related to customer satisfaction was partially accepted. A single factor was found from the exploratory Factor Analysis on customer loyalty; this was termed ―New Age Loyalty”. As a result of two dimensions related to customer loyalty being excluded from the final factor solution, namely the patrons‘ ―propensity to switch‖ and the patrons‘ ―complaint behaviour‖, the research proposition was also partially accepted. ii Interdependence Factor Analysis was performed in order to determine what, if any, correlations exist between the dimensions of customer satisfaction and customer loyalty. Three factors were found which can describe the correlations between these two constructs namely, “Physical Store Attributes versus Spurious Bond”, “Convenient Value versus Attitudinal Bond”, and "Consumption Behaviours versus Emotional Bond", accordingly the research proposition was accepted. In addition a fourth factor, ―No Bond” is proposed by the researcher based on work done by Dick and Basu (1994). The findings further indicate that there are a number of dimensions of both customer satisfaction and loyalty which the retailer can, in fact, influence. In so doing retailers are able to play a pivotal role in shaping patronage behaviours as manifested in differing forms and strengths of loyalty. These differing forms and strengths of loyalty are largely determined by the nature of the competitive landscape in which the retailer operates and the value proposition offered by the retailer. The development of an ―emotional bond‖ or an ―attitudinal bond‖ with the store ultimately leads to repeat purchasing by the store‘s patrons and wealth creation for the retailer, whilst the development of a ―spurious bond‖ or ―no bond‖ only serves to increase retailer costs, and results in eventual switching by the store patron. It is evident from the research that the constructs of both customer satisfaction and loyalty are evolving over time. This was most noticeable in the dimensions of each construct which were not included in the final solutions, although they were apparent in the literature review and other research. It is therefore pertinent to highlight that the customer satisfaction and loyalty dimensions, and any association between the two, are as much a function of the competitive landscape in which the retailer operates and value offered by the retailer, as they are a function of time and with the passing of time, they will change
MBA - WBS
Keywords: Customer loyalty; Customer satisfaction; Retail stores